CLINICAL HYPOGLYCEMIC EFFECTS OF ALLIUM CEPA (RED ONION) IN TYPE 2 DIABETIC PATIENTS - Taj Eldin, Imad M.; Ahmed, Elhadi M.; HM, Abd Elwahab (Gezira Journal of Health Sciences, 2009)
Background : Type 2 diabetes mellitus results from defects in insulin secretion and/or insulin action or both. Objectives: The present study was conducted to investigate the hypoglycemic effects of Allium cepa in patients with type 2 diabetes mellitus.   Results: In type 2 diabetic patients (n=21) the administration of crude Allium cepa (100g) markedly reduced fasting blood glucose levels by 40 mg/dl 4 hours later, compared to glibenclamide (81 mg/dl). Also Allium cepa significantly reduced the induced hyperglycemia (GTT) after ingestion of 75 grams dextrose by 159 mg/dl in the test subgroup (n=7) of type 2 diabetic patients to a point below that produced in the negative control group after 4 hours. Conclusion: Crude Allium cepa produced hypoglycemic effects, thus it could be used as a dietary supplement in management of diabetes.